Big box battles: the Ontario Municipal Board and large-format retail land-use planning conflicts in the Greater Toronto Area - Webber, Steven; Hernandez, Tony (International planning studies, 2016)
The Ontario Municipal Board is a quasi-judicial tribunal that is responsible for adjudicating municipal land-use planning appeals. The Board exerts considerable influence over property development outcomes. Big box retail as a form of commercial development has often been subject to planning conflict and appeal. This paper examines 65 big box retail Board appeals filed between 1993 and 2012 by developers and stakeholders independently or jointly in response to applications submitted at the municipal level throughout the Greater Toronto Area, Canada's largest metropolitan market. Results indicate the presence of game playing strategies used by participants that involves leveraging the potential of proceeding with a potentially expensive, time-consuming and uncertain hearing as a means to negotiate a settlement.